2008
DOI: 10.1677/joe-08-0421
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the V1b receptor reduces ACTH, but not corticosterone secretion induced by stress without affecting basal hypothalamic–pituitary–adrenal axis activity

Abstract: Vasopressin (AVP), produced in parvocellular neurons of the hypothalamic paraventricular nucleus, regulates, together with CRH, pituitary ACTH secretion. The pituitary actions of AVP are mediated through the G protein receptor V 1b (V 1b jR). In man, hyperactivity of the hypothalamicpituitary-adrenal axis has been associated with depression and other stress-related conditions. There are also clinical data suggesting a role for AVP in the dysfunctional HPA axis described in some depressed patients. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 58 publications
(46 reference statements)
10
29
0
Order By: Relevance
“…It was surprising as AVP shows circadian rhythms of synthesis and release within the suprachiasmatic nucleus (Engelmann et al 1998), so its absence could have disturbed the daily rhythms of HPA axis hormone production as well. However, on the basis of the present results it seems that the lack of AVP in Brattleboro rats does not influence the pattern of the secretion, similar to results in V1b receptor KO mice (Lolait et al 2007a) and in rats given the V1b receptor antagonist (Spiga et al 2009). …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It was surprising as AVP shows circadian rhythms of synthesis and release within the suprachiasmatic nucleus (Engelmann et al 1998), so its absence could have disturbed the daily rhythms of HPA axis hormone production as well. However, on the basis of the present results it seems that the lack of AVP in Brattleboro rats does not influence the pattern of the secretion, similar to results in V1b receptor KO mice (Lolait et al 2007a) and in rats given the V1b receptor antagonist (Spiga et al 2009). …”
Section: Discussionsupporting
confidence: 83%
“…In vitro studies show both that cAMP content (C; due to 5!10 K8 M CRH; nZ9-10) and ACTH secretion (D; due to 5-10 K11 M CRH; nZ10-11) were enhanced by CRH with a smaller ACTH response in di/di rats. found in studies using the V1b receptor antagonist (Org) in Sprague-Dawley rats (Spiga et al 2009) and in the V1b receptor KO mice (Stewart et al 2008), demonstrating that phenomenon is not species specific. The fact that the discrepancy between ACTH and corticosterone could not be explained by ACTH sensitivity or missed time points raises the possibility that other peripheral mediators are involved and may be acting directly on the adrenal gland.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have recently shown that this AVPR1B antagonist can reduce ACTH and corticosterone responses to exogenous AVP in rats (Spiga et al 2008). Furthermore, in the same report, we have shown that the same compound is able to reduce ACTH release induced by acute exposure to stress.…”
Section: Introductionsupporting
confidence: 52%
“…4). We have recently shown that this compound, injected 30 min prior to AVP, is able to reduce both ACTH and corticosterone response to AVP (Spiga et al 2008). Thus, this time point for Org administration in relation to both stress and AVP was used in the present study.…”
Section: Methodsmentioning
confidence: 99%